Renewable VOCs adsorbent based on shale gas drilling oil base rock debris deoiling residues and preparation and regeneration method thereof

Renewable VOCs adsorbents are prepared by grinding, pickling, alkali washing and alkali fusion reaction of the deoilated residue of shale gas drilling oil bedrock chips, and regeneration of the adsorbents is achieved through short-term heat treatment under normal pressure, which solves the problem of difficulty in effectively utilizing the deoilated residue in the prior art, and achieves efficient and economical VOCs adsorption effect and recycling of adsorbents.

CN119633746APending Publication Date: 2025-03-18PUYANG TIANDIREN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411935744.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize shale gas drilling oil bedrock deoiling residues, especially in the preparation of renewable VOCs adsorbents, and the existing regeneration methods are costly and time-consuming.

Method used

Renewable VOCs adsorbents are prepared by grinding, pickling, alkaline washing, alkaline melting and roasting, and regeneration of the adsorbents is achieved by short-term heat treatment under normal pressure.

Benefits of technology

It realizes the rapid regeneration and utilization of VOCs adsorbents in ordinary environments, reduces energy consumption, reduces the emission of oil bedrock chips, and converts them into high-value adsorbents, effectively adsorbing VOCs, achieving the goal of "treat waste with waste".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633746A_ABST
    Figure CN119633746A_ABST
Patent Text Reader

Abstract

The invention relates to the field of solid waste resource utilization, in particular to a renewable VOCs adsorbent based on shale gas drilling oil base rock debris deoiling residues and a preparation and regeneration method thereof.The preparation method comprises the steps that the deoiling residues are subjected to first grinding and sieving, sieved powder is collected, and deoiling residue powder is obtained; carrying out acid pickling on the deoiled residue powder by using an acid solution, and centrifugally collecting an acidic precipitate; washing the acidic precipitate with an alkali solution to be neutral, and drying to obtain impurity-removed powder; mixing the impurity-removed powder with sodium hydroxide, adding aluminum hydroxide, and grinding to obtain an alkali fusion reaction system; roasting and cooling the alkali melting reaction system to obtain an alkali melting product; adding deionized water into the alkali melting product, stirring and standing, and collecting a precipitate; and crystallizing the precipitate in a reaction kettle, washing, carrying out suction filtration, and drying to obtain the renewable VOCs adsorbent. According to the method disclosed by the invention, the resource utilization of the deoiling residues is realized, and the recycling of the VOCs adsorbent can be completed through short-time heat treatment in a common environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solid waste resource utilization, and specifically to a renewable VOCs adsorbent based on shale gas drilling oil-based cuttings deoiling residue and a preparation and regeneration method thereof. Background Art

[0002] Shale gas drilling oil-based cuttings contain a lot of mineral oil and have been included in the "National List of Hazardous Wastes 2021 Edition". Pyrolysis is an important method for treating oil-based cuttings at home and abroad. After treatment, the remaining solid phase-oil-based cuttings deoiling residue is finally produced. However, since the oil-based cuttings deoiling residue may still have biological toxicity, its rational resource utilization has attracted widespread attention. At present, the main resource utilization of oil-based cuttings deoiling residue is mainly concentrated in the field of building materials utilization, mainly including cement kiln co-disposal, concrete preparation, brick making, roadbed material preparation, construction ceramsite preparation and other resource processing technologies. Although the oil-based cuttings deoiling residue can be disposed of as a building material, it is easily restricted by the development of the building materials industry, and the market value of the building material product as a resource is not high.

[0003] As a mineral rich in silicon and aluminum, shale gas drilling oil-based cuttings meet the chemical composition required for the preparation of zeolite molecular sieve adsorbents and can be used as raw materials for zeolite-like adsorbent materials. Using the deoiled residue of shale gas drilling oil-based cuttings to prepare adsorbent materials is one of the ways to convert and utilize them at a high value. Prior art CN201810011878.3 has demonstrated the feasibility of using shale gas oil-based drilling cuttings pyrolysis ash as raw material to prepare zeolite, but it has not verified the adsorption effect of artificial zeolite on VOCs. Prior art CN108607499A discloses a method for preparing an ozone-regenerable adsorbent, but during regeneration, it is necessary to perform a 24-hour 10°C hot air purge in a 100°C environment with continuous ozone introduction, which is costly and takes a long time to regenerate.

[0004] Therefore, a new method for preparing VOCs adsorbents is needed to fill the current technical gap in preparing VOCs adsorbents based on deoiling residues and to achieve the regeneration of VOCs adsorbents at a faster speed under normal conditions. Summary of the invention

[0005] The problem that the present application aims to solve is to provide a renewable VOCs adsorbent based on the deoiling residue of oil-based rock cuttings from shale gas drilling, and a preparation and regeneration method thereof, so as to realize the resource utilization of the deoiling residue, and to complete the regeneration of the VOCs adsorbent through a short period of heat treatment under normal conditions.

[0006] In order to solve the above technical problems, this application adopts the following technical solutions:

[0007] On the one hand, the present application provides a method for preparing a renewable VOCs adsorbent based on shale gas drilling oil-based cuttings deoiling residue, comprising the following steps:

[0008] The de-oiled residue is first ground and sieved, and the sieved powder is collected to obtain the de-oiled residue powder; the de-oiled residue powder is acid-washed and centrifuged with an acid solution, and the acid precipitate is collected; the acid precipitate is washed with an alkaline solution to neutrality and then dried to obtain a de-impurity powder; the de-impurity powder is mixed with sodium hydroxide, and then aluminum hydroxide is added for grinding to obtain an alkali-melt reaction system; the alkali-melt reaction system is roasted and cooled to obtain an alkali-melt product; deionized water is added to the alkali-melt product, and the precipitate is collected after stirring and standing; and the precipitate is transferred to a reactor for crystallization, washing, suction filtration and drying to obtain the renewable VOCs adsorbent.

[0009] Furthermore, the weight ratio of the impurity-removing powder to the sodium hydroxide is 1:(1.2-1.4).

[0010] Furthermore, the silicon-aluminum ratio in the alkali melting reaction system is (1-3):1.

[0011] Furthermore, the screening is carried out on a 100-mesh sieve.

[0012] Furthermore, the acid solution comprises a hydrochloric acid solution with a mass fraction of 5% to 10%.

[0013] Furthermore, the alkaline solution includes a sodium hydroxide solution with a mass fraction of 10%.

[0014] Furthermore, the pickling temperature is 80-85° C., and the pickling time is 2 hours.

[0015] Furthermore, the calcination temperature is 300-350° C., and the calcination time is 2-4 hours.

[0016] Furthermore, the crystallization temperature is 100 to 120° C., and the crystallization time is 3 to 24 hours.

[0017] Furthermore, the amount of the deionized water used is 1.2 to 1.4 times the sum of the mass of the impurity-removing powder and the sodium hydroxide.

[0018] On the other hand, the present application provides a renewable VOCs adsorbent prepared by the above preparation method.

[0019] In another aspect, the present application provides a renewable VOCs adsorbent prepared by the above preparation method or a method for regenerating the above renewable VOCs adsorbent, comprising the following steps:

[0020] The regenerated VOCs adsorbent after use is subjected to heat treatment for 20 minutes under normal pressure to obtain a regenerated VOCs adsorbent.

[0021] Furthermore, the heat treatment temperature is 350°C.

[0022] This application has the following beneficial effects:

[0023] (1) When the preparation method provided in the present application uses shale gas drilling oil-based cuttings to prepare a renewable VOCs waste gas adsorbent, the calcination and crystallization temperatures are low and the reaction time is short, which greatly reduces energy consumption;

[0024] (2) This application makes full use of the oil-based cuttings generated by shale gas drilling and converts them into non-toxic and harmless renewable VOCs adsorbents with high market value, which can greatly reduce the emission of oil-based cuttings;

[0025] (3) The renewable VOCs adsorbent prepared in the present application can effectively adsorb VOCs, achieving the effect of treating waste gas pollution with solid waste and realizing the purpose of "treating waste with waste".

[0026] (4) The renewable VOCs adsorbent prepared in the present application can restore its adsorption capacity and maintain a high activity by heat treatment for 20 minutes at normal pressure after use, thereby realizing the recycling of the adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a process flow chart for preparing a renewable VOCs adsorbent based on the deoiling residue of shale gas drilling oil-based cuttings in this application. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.

[0029] Example 1

[0030] The residue after de-oiling from shale gas drilling oil-based cuttings pyrolysis treatment was used as raw material, and the silicon and aluminum elements in the de-oiled residue were analyzed by XRF. The analysis results are shown in Table 1.

[0031] Table 1

[0032] element Si Al Element percentage (%) 28.331 8.6112

[0033] Example 2

[0034] Follow the steps below to prepare the regenerable VOCs adsorbent:

[0035] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and then sieved using a 100-mesh sieve, and the sieved powder was collected to obtain a de-oiled residue powder;

[0036] S12. The deoiled residue powder was acid washed with 10% hydrochloric acid at 85°C for 2 h, and then centrifuged at 2000 rpm for 10 min to collect the acid precipitate;

[0037] S13. The acidic precipitate is washed to neutrality with a 10% sodium hydroxide solution and dried to obtain a decontaminated powder;

[0038] S14. 6 g of sodium hydroxide was added to 5 g of the impurity-removing powder and mixed, and then aluminum hydroxide was added until the Si:Al in the mixture was 1:1, and then ground to obtain an alkali melt reaction system;

[0039] S15. The alkali-melt reaction system was placed in a muffle furnace and calcined at 300 ° C for 2h to obtain an alkali-melt product;

[0040] S16. Add 13.2 mL of deionized water to the alkali-melted product, stir at room temperature for 3 h, let stand for 30 min, and collect the precipitate;

[0041] S17. The precipitate is transferred to a reactor, and after crystallization in an oven at 100°C for 3 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100°C and dried for 120 minutes to obtain the renewable VOCs adsorbent.

[0042] Example 3

[0043] Follow the steps below to prepare the regenerable VOCs adsorbent:

[0044] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and then sieved using a 100-mesh sieve, and the sieved powder was collected to obtain a de-oiled residue powder;

[0045] S12. The deoiled residue powder was acid washed with 5% hydrochloric acid at 80°C for 2 h, and then centrifuged at 2000 rpm for 10 min to collect the acid precipitate;

[0046] S13. The acidic precipitate is washed to neutrality with a 10% sodium hydroxide solution and dried to obtain a decontaminated powder;

[0047] S14. 6.5 g of sodium hydroxide was added to 5 g of the impurity removal powder and mixed, and then aluminum hydroxide was added until the Si:Al in the mixture was 2:1, and then ground to obtain an alkali melt reaction system;

[0048] S15. The alkali-melt reaction system was placed in a muffle furnace and calcined at 325 ° C for 3h to obtain an alkali-melt product;

[0049] S16. Add 15 mL of deionized water to the alkali-melted product, stir at room temperature for 3 h, let stand for 30 min, and collect the precipitate;

[0050] S17. The precipitate is transferred to a reactor, and after crystallization in an oven at 110°C for 12 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100°C and dried for 120 minutes to obtain the renewable VOCs adsorbent.

[0051] Example 4

[0052] Follow the steps below to prepare the regenerable VOCs adsorbent:

[0053] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and then sieved using a 100-mesh sieve, and the sieved powder was collected to obtain a de-oiled residue powder;

[0054] S12. The deoiled residue powder was acid washed with 5% hydrochloric acid at 80°C for 2 h, and then centrifuged at 2000 rpm for 10 min to collect the acid precipitate;

[0055] S13. The acidic precipitate is washed to neutrality with a 10% sodium hydroxide solution and dried to obtain a decontaminated powder;

[0056] S14. 7 g of sodium hydroxide was added to 5 g of the impurity-removing powder and mixed, and then aluminum hydroxide was added until the Si:Al in the mixture was 3:1, and then ground to obtain an alkali melt reaction system;

[0057] S15. The alkali-melt reaction system was placed in a muffle furnace and calcined at 350 ° C for 4 h to obtain an alkali-melt product;

[0058] S16. Add 16.8 mL of deionized water to the alkali-melted product, stir at room temperature for 3 h, let stand for 30 min, and collect the precipitate;

[0059] S17. The precipitate is transferred to a reactor, and after crystallization in an oven at 120°C for 24 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100°C and dried for 120 minutes to obtain the renewable VOCs adsorbent.

[0060] Example 5 Verification of the adsorption effect of the renewable VOCs adsorbent on the simulated gas containing toluene

[0061] The renewable VOCs adsorbent prepared in Examples 2 to 4 was placed in a tubular furnace quartz tube adsorption column, and both ends were sealed with quartz wool. The adsorption temperature was controlled to 40°C by programming the tubular furnace; a simulated gas (containing 0.1% toluene, 78.1% nitrogen, and 21.8% oxygen) was introduced, and the outlet toluene concentration was measured by a gas chromatograph. When the adsorption column was saturated with adsorption, the toluene concentration in the tail gas was almost equal to the inlet concentration, that is, C / C0=1. C / C0=0.05 is used as the penetration concentration standard for dynamic adsorption of toluene, and the time at this time is the penetration time of toluene. In general, the longer the penetration time, the better the adsorption performance of the sample. The saturated adsorption amount of VOCs q m The following formula is used for calculation and the calculation results are shown in Table 2.

[0062]

[0063] Among them, q m —Saturated adsorption capacity (mg / g);

[0064] F—gas flow rate (m 3 / min);

[0065] m—mass of regenerable VOCs adsorbent (g);

[0066] C0—inlet gas concentration (mg / m 3 );

[0067] C—Outlet gas concentration (mg / m 3 );

[0068] t—adsorption time (min).

[0069] Table 2: Adsorption effect of various renewable VOCs adsorbents on toluene.

[0070] project Breakthrough time (min) Saturated adsorption capacity (mg / g) Example 2 31.6 41.46 Example 3 30.5 40.79 Example 4 32.4 43.28

[0071] According to Table 2, the present application uses the de-oiled residue of shale gas drilling oil-based cuttings as raw material to prepare a renewable VOCs adsorbent. When the slag-alkali ratio is 1:1.4, the silicon-aluminum ratio is 2:1, the calcination temperature is 350°C, the amount of deionized water is 1.4 times that of the molten product, and the crystallization time is 24h, the obtained adsorbent has the best adsorption effect on toluene, the adsorption penetration time is 32.4min, and the adsorption amount of the adsorbent when saturated reaches 43.28mg / g. The renewable VOCs adsorbent prepared in Example 4 is selected for subsequent experiments.

[0072] Example 6 Verification of the adsorption effect of the renewable VOCs adsorbent on simulated gases containing toluene at different concentrations

[0073] 1 g of the renewable VOCs adsorbent prepared in Example 4 was respectively placed in three tubular furnace quartz tube adsorption columns, both ends of which were blocked with quartz wool, and the adsorption temperature was controlled to be 40°C by programming the tubular furnace; simulated gas 1 (0.1% toluene, 78.1% nitrogen, 21.8% oxygen), simulated gas 2 (0.2% toluene, 78.1% nitrogen, 21.7% oxygen) and simulated gas 3 (0.3% toluene, 78.1% nitrogen, 21.6% oxygen) were respectively introduced into the three quartz tubes, and the toluene concentration in the outlet gas was analyzed by gas chromatograph, and the breakthrough time and saturated adsorption amount were calculated. The results are shown in Table 3.

[0074] Table 3: Adsorption effect of renewable VOCs adsorbent on simulated gases containing toluene at different concentrations

[0075] project Breakthrough time (min) Saturated adsorption capacity (mg / g) Simulated gas 1 32.4 43.28 Simulated gas 2 17.8 51.34 Simulated gas 3 9.8 60.21

[0076] According to Table 3, the saturated adsorption capacity of the renewable VOCs adsorbent prepared in Example 4 for simulated gases containing toluene at different concentrations is 43.28-60.21 mg / g, and the penetration time is 9.8-32.4 min.

[0077] Example 7 Verification of the adsorption effect of the regenerable VOCs adsorbent on toluene-containing simulated gas at different temperatures

[0078] 1 g of the renewable VOCs adsorbent prepared in Example 4 was respectively placed in three tubular furnace quartz tube adsorption columns, both ends of which were blocked with quartz wool, and the adsorption temperatures were controlled by programming the tubular furnace to be 40°C, 50°C, and 60°C, respectively; simulated gas (0.1% toluene, 78.1% nitrogen, 21.8% oxygen) was introduced, and the concentration of toluene in the outlet gas was analyzed by gas chromatograph, and the breakthrough time and saturated adsorption amount were calculated. The results are shown in Table 4.

[0079] Table 4: Adsorption effect of regenerable VOCs adsorbents at different temperatures on simulated gases containing toluene at different concentrations

[0080] Adsorption temperature (℃) Breakthrough time (min) Saturated adsorption capacity (mg / g) 40 32.4 43.28 50 27.7 34.34 60 24.1 29.22

[0081] According to Table 4, the toluene saturation adsorption capacity of the renewable VOCs waste gas adsorbent prepared in Example 4 for toluene-containing simulated gas at different temperatures is 29.22-43.28 mg / g, and the penetration time is 24.1-32.4 min.

[0082] Example 8 Adsorption effect of regenerable VOCs adsorbent after regeneration

[0083] S21. Take 1g of the renewable VOCs adsorbent prepared in Example 4 and place it in a tubular furnace quartz tube adsorption column. Both ends are blocked with quartz wool. The adsorption temperature is controlled to be 40°C by programming the tubular furnace. Simulated gas (0.1% toluene, 78.1% nitrogen, 21.8% oxygen) is introduced. The concentration of toluene in the outlet gas is analyzed by gas chromatograph. The breakthrough time and saturated adsorption amount are calculated. When the toluene concentration in the tail gas is almost equal to the inlet concentration, the intake is stopped;

[0084] S22. After the air intake is stopped, the temperature in the quartz tube is raised to 350°C within 10 minutes through the tubular furnace programming, and after the heating is maintained for 20 minutes, it is cooled to 40°C to obtain the regenerated adsorbent;

[0085] S23. The regenerated adsorbent was subjected to four repeated adsorption and regeneration experiments;

[0086] S24. Collect and record the breakthrough time and saturated adsorption amount of simulated exhaust gas 5 times. The results are shown in Table 5.

[0087] Table 5:

[0088] Repetitions Breakthrough time (min) Saturated adsorption capacity (mg / g) 0 32.4 43.28 1 32.0 43.17 2 31.1 42.56 3 31.0 42.50 4 30.2 41.60

[0089] According to the results, the treatment capacity of the VOCs adsorbent for toluene-containing simulated gas after multiple regenerations did not change much. The penetration time of the VOCs adsorbent decreased from 32.4 min to 30.2 min, an overall decrease of 6.7%; the saturated adsorption capacity decreased from 43.28 mg / g to 41.60 mg / g, an overall decrease of 3.8%.

[0090] In summary, the method provided in the present application can convert the de-oiling residue into a VOCs adsorbent with usable value at a lower temperature. The obtained VOCs adsorbent has an excellent volatile organic compound adsorption effect, realizing the waste utilization of the de-oiling residue. The regenerated VOCs adsorbent obtained by the regeneration method provided in the present application has an adsorption effect that is not much different from that of a new adsorbent. After multiple regenerations, it can still ensure that the penetration time and adsorption effect of the VOCs adsorbent remain at a high level.

[0091] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a renewable VOCs adsorbent based on deoiling residues of oil-based cuttings from shale gas drilling, characterized in that: The following steps are involved: The de-oiled residue is first ground and sieved, and the sieved powder is collected to obtain the de-oiled residue powder; The de-oiled residue powder is acid-washed and centrifuged using an acid solution to collect an acid precipitate; The acidic precipitate is washed with an alkaline solution until it becomes neutral and then dried to obtain a decontaminated powder; The impurity-removing powder is mixed with sodium hydroxide, and then aluminum hydroxide is added and ground to obtain an alkali-melting reaction system; The alkali-melt reaction system is calcined and cooled to obtain an alkali-melt product; Adding deionized water to the alkali-melted product, stirring and standing the product to collect the precipitate; as well as The precipitate is transferred to a reactor for crystallization, washing, suction filtration and drying to obtain the renewable VOCs adsorbent; Wherein, the weight ratio of the impurity-removing powder to the sodium hydroxide is 1:(1.2-1.4); And / or, the silicon-aluminum ratio in the alkali melting reaction system is (1-3):

1.

2. The preparation method according to claim 1, characterized in that: The sieving is performed using a 100-mesh sieve.

3. The preparation method according to claim 1, characterized in that: The acid solution comprises a hydrochloric acid solution with a mass fraction of 5% to 10%; And / or, the alkaline solution comprises a sodium hydroxide solution with a mass fraction of 10%.

4. The preparation method according to claim 1, characterized in that: The pickling temperature is 80-85°C and the pickling time is 2h; And / or, the calcination temperature is 300-350°C, and the calcination time is 2-4h; And / or, the crystallization temperature is 100-120° C., and the crystallization time is 3-24 hours.

5. The method according to claim 1, characterized in that The amount of the deionized water used is 1.2 to 1.4 times the sum of the mass of the impurity-removing powder and the sodium hydroxide.

6. A regenerable VOCs adsorbent obtained by the preparation method according to any one of claims 1 to 5.

7. The regenerable VOCs adsorbent prepared by the preparation method according to any one of claims 1 to 5 or the regeneration method of the regenerable VOCs adsorbent according to claim 6, characterized in that: The following steps are involved: The regenerated VOCs adsorbent after use is subjected to heat treatment for 20 minutes under normal pressure to obtain a regenerated VOCs adsorbent.

8. The regeneration method according to claim 7, characterized in that: The temperature of the heat treatment is 350°C.

Citation Information

Patent Citations

  • Preparation method and products of zeolite from oil-based drill cuttings pyrolysis ash

    CN108046284B

  • Preparation method of ozone renewable absorbent

    CN108607499A